Peran Sektor Berbasis Industri Pada Perekonomian Provinsi Jawa Timur (Pendekatan Input-Output) - Santoso, Edy (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2017)
The development of industrial sector strongly is essential for sustained and quality economic growth. Based on the role of the industrial sectors are significant in economy, it is reasonable to say that the industrial sector is said to be a strategic sector based on its ability to trigger economic growth. The aims for this study are: (1) to know the role of industry-based sector in the economy of East Java Province, 2). to know which sector can be made as a leading sector so that it can be prioritized in its development. Using input output models to analyze the linkages and multiplier for each industry-based sector. The result of the study shows that the role of the sector is seen from foward linkages effect, the non-classified goods industry sector and the chemical industry are industries with a high forward linkages effect. While the rice milling industry sector is the sector with the highest backward linkages effect. The sector with the highest output multiplier impact is the rice mill industry. The pesticide fertilizer industry sector has the highest income multipliers impact. The cigarette industry is the sector with the largest contribution to the export of East Java Province. The paper industry is the sector with the highest import contribution, followed by the cigarette industry. For the twenty-four industry-based sectors in the East Java economy, the rice milling sector and the sugar industry sector are potential sectors to be developed.